Dimensions of bilingual education program implementation in schools serving linguistically minoritized students in the Czech-Polish border region - Hopkins, Megan; Nowak-Żółty, Edyta; Kurowska-Pysz, Joanna; Szyszka, Michał (Frontiers in Education, 2023)
Introduction A core challenge for the implementation of bilingual programs is ensuring that linguistically minoritized students have equitable access to instruction that honors and values their linguistic and cultural assets and strengths. To understand how leaders of bilingual programs might address this challenge, this study sought to identify dimensions of program implementation in bilingual schools serving Polish minorities in the Zaolzie region on the Czech Republic side of the Czech-Polish border. Methods Employing a sequential explanatory mixed methods design, the research team first collected surveys from 123 teachers and used factor analytical techniques to identify key dimensions of program implementation. Then, interview and observational data were collected and analyzed using deductive coding to develop descriptions of each dimension in this specific border region. Results The analysis revealed four dimensions of program implementation: (a) program structure and alignment; (b) culturally and linguistically responsive instruction; (c) staff quality and professional learning; and (d) family engagement and community support. They also showed how a network of community-based organizations partnered with schools and families in ways that supported each dimension and facilitated integration across dimensions. Discussion The findings have several implications for leaders and researchers in bilingual schools including the important role that community organizations and binational cooperation can play in positively contributing to the education of linguistically minoritized populations.